Fast and Automatic Control of a Frequency-Tuned Radiofrequency Plasma Source - Takahashi, Kazunori; Hanaoka, Kengo; Ando, Akira (Frontiers in Physics, 2020)
A frequency-tuned radiofrequency (rf) plasma source is automatically controlled to minimize the rf power reflection and to maintain the constant net rf power corresponding to the forward power minus the reflected power. The experiment is performed with a power amplifier operational for the frequency of 37–43 MHz, a compact helicon source consisting of a loop antenna, a solenoid, and an insulator tube. The rf power is supplied to the rf antenna via an impedance matching circuit consisting of only fixed small ceramic capacitors. It is demonstrated that the reflection coefficient of the rf power is minimized within ~10 ms, and the net power is successfully maintained at a constant level.